From Skill Acquisition to Professional Agency: Rethinking EFL Teachers’ Professional Development in the Age of AI - Hamed Barjesteh; Hossein Isaee; Mehdi Manoochehrzadeh (Indonesian Journal of Pedagogy and Teacher Education, 2026)
Background: The rapid emergence of artificial intelligence (AI)–assisted tools has begun to reshape English as a Foreign Language (EFL) teaching practices, raising new questions about teachers’ roles, autonomy, and professional growth. While previous research has addressed professional development (PD) needs in traditional and online contexts, limited attention has been given to AI-mediated teaching environments. Aims: This study aims to explore EFL teachers’ perceptions and lived experiences of AI-assisted language teaching, particularly in relation to professional agency, identity, and emerging professional development needs. Methods: This study adopted a qualitative interpretive phenomenological approach. Data were collected through in-depth semi-structured interviews with 10 experienced EFL teachers who had engaged with AI tools in instructional, assessment, or material development practices. The data were analyzed using reflexive thematic analysis. Results: The findings reveal that teachers perceive AI as both a pedagogical support and a source of professional tension. While AI enhances efficiency, feedback provision, and instructional design, it also raises concerns related to loss of control, ethical responsibility, assessment validity, and role ambiguity. Teachers continuously negotiate their professional agency and identity when integrating AI into their practices. Furthermore, traditional PD frameworks are found to be insufficient in addressing these challenges. Conclusion: The study highlights the need to reconceptualize EFL teacher professional development by emphasizing critical AI literacy, ethical awareness, and agency-oriented pedagogical decision-making. Professional development should move beyond technical training to support teachers as reflective and autonomous professionals in AI-mediated educational environments.